Pengaruh Literasi Keuangan Syariah, Layanan Mobile Banking dan Shariah Compliance Terhadap Minat Menabung pada Bank Syariah dengan Religiusitas Sebagai Variabel Moderasi: Studi Kasus Pada Mahasiswa Ekonomi Islam Surabaya - Tegar Qodri Nugroho; Ach Yasin (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to determine the influence of sharia financial literacy, mobile banking services, and sharia compliance on interest in saving at sharia banks with religiosity as a moderating variable (case study of Islamic Economics students in Surabaya). The data used is primary data through distributing questionnaires. The sample used was 370 respondents who were randomly selected based on certain criteria using purposive sampling techniques. The research results show that sharia financial literacy, mobile banking services, and sharia compliance have a significant effect on interest in saving at sharia banks. Meanwhile, religiosity can strengthen the influence of sharia financial literacy on interest in saving at sharia banks. The results of testing the coefficient of determination showed that sharia financial literacy, mobile banking services and sharia compliance had a simultaneous influence of 72% on interest in saving at sharia banks.